Two concepts of practice and theology - Afdal, Geir (Studia theologica, 2021)
Practice and practices have been increasingly discussed in theology. In these discussions, practice is often understood in relation to theory. In emergent practice theory, however, practice is understood in terms of social ontology and as an alternative to methodological individualism and methodological holism. Society, including religion, is analysed as nexuses of collective practices. This article makes a distinction between two concepts of practice, one weak and one strong, and discusses these concepts in texts by Kathlyn Tanner and Linda Woodhead. It also discusses how a strong conception of practice may contribute to theology.